Structural properties of the glycoplasmanylinositol anchor phospholipid of the complement membrane attack complex inhibitor CD59. - Ratnoff, W D (1992)
CD59, the membrane regulator of autologous C5b-9 channel formation, exhibits variable sensitivity to cleavage by phosphatidylinositol-specific phospholipase C (PI-PLC), an enzyme that releases glyco-inositolphospholipid (GPI)-anchored proteins from cell surfaces. To determine whether the GPI-anchor phospholipid of CD59 is similar to that of decay-accelerating factor (DAF) and whether variation in its structure underlies its variable enzyme susceptibility, the GPI anchors of the two proteins expressed on erythrocytes, polymorphonuclear and mononuclear leucocytes were compared in situ and after purification. Flow cytometric analyses of PI-PLC-treated cells showed parallel cell type specific release of both proteins as a function of enzyme concentration. Non-denaturing PAGE analyses of alkaline/hydroxylamine-treated proteins (affinity-purified from [125I]-surface-labelled cells) provided evidence for (i) comparable proportions of GPI-anchor acylation, and (ii) alkali-resistant rather than alkali-sensitive lipid substituents in erythrocytes. These findings argue that the differential C5b-9 sensitivity that distinguishes paroxysmal nocturnal haemoglobinuria II and III erythrocytes does not derive from expression of CD59 molecules with alternative GPI-anchor phospholipid structures.